Creative writing in organization teaching of the construction site - Fontenelle , Maria Aridenise Macena; Souza, Eloi Romão dos Santos (Seven Editora, 2023)
This article presents the creative writing strategies used by students of the discipline of Construction Technology of the Civil Engineering course of a university in the Brazilian Northeast to present the learning outcome in this discipline. The summaries were written in verse form by the students from the reflection of reading documents in the content area of the discipline and the understanding of the videos watched by them on the same topic. The results showed a good performance of the class in addition to the technical knowledge for the activation of the sensitive. The students considered that creative writing brought more lightness to the teaching and learning process in the organization of the construction site. DOI:https://doi.org/10.56238/ptoketheeducati-018